Rivastigmine improves dual-task gait velocity in patients with Alzheimer’s disease - Shimura, Hideki (BMC Neurol, 2021)
BACKGROUND: Gait impairments are common in patients with Alzheimer’s disease. Cholinesterase inhibitors are used to treat the symptoms of patients with Alzheimer’s disease, but they have not been shown to reduce the severity of Alzheimer’s disease-related gait disorders. METHODS: This was a prospective, single-arm, open-label, non-randomized study. The aim of the present study was to determine the effect of the acetylcholinesterase inhibitor rivastigmine on gait in 21 newly diagnosed patients with mild to moderate Alzheimer’s disease. The outcome variables were velocity, stride length, and cadence during single-task and dual-task gait trials. The subjects were also assessed with the Mini-Mental State Examination, Alzheimer’s Disease Cooperative Study Activities of Daily Living, Functional Assessment Staging, and Geriatric Depression Scale. RESULTS: After 12 weeks of treatment with rivastigmine, gait velocity was significantly improved in the dual-task gait trials; gait velocity was increased from 40.59 ± 13.59 m/min at baseline to 46.88 ± 12.73 m/min when counting backward from 100 in steps of 7 while walking, and gait velocity was increased from 37.06 ± 15.57 m/min at baseline to 42.03 ± 14.02 m/min when naming animals while walking. In the single-task gait trials, which consisted only of walking at their usual pace or at a fast pace, gait velocity was not increased by rivastigmine administration. CONCLUSION: Our findings indicated that rivastigmine improved gait in subjects with mild to moderate Alzheimer’s disease during dual-task trials. The observed enhancement of dual-task gait might be caused by an improvement of cognitive function rather than motor function. TRIAL REGISTRATION: UMIN, UMIN000025869. Registered December 16, 2016, https://upload.umin.ac.jp/cgi-open-bin/icdr/ctr_view.cgi?recptno=R000029744